(untitled) (Fiep Bulletin - online, 2011)
It is known that adequate stimulation of motor coordination in children with intellectual disabilities is an important component of development best suited. Moreover, it is known that this stimulation could and should be implemented in schools by teachers of Physical Education after proper assessment of motor function. Still, few scientific studies specifically address the benefits and strategies for the practice. This study aims to examine the benefits that the adapted physical education classes can bring to the improvement of motor coordination in children and adolescents with mental disabilities. For this, we researched the test KTK (Körperkoordination Test für Kinder), which consists of four events: balance beam, one leg jumps, lateral jumps and transfer platform. Its application becomes feasible in schools due to easy implementation and low cost of materials. Taking into account the studies and considerations of the authors, the results indicate that applications of different programs of physical activity showed benefits for the coordination, by applying the test KTK. It succeeded a careful diagnosis, leading to decisions on the problems presented by the students, making it easier for an intervention and planning activities on the basis of these difficulties. It found that classes in Adapted Physical Education provide improved motor coordination in children and adolescents with mental disabilities.